2005
DOI: 10.1007/s11136-004-1920-6
|View full text |Cite
|
Sign up to set email alerts
|

Proxy completion of EQ-5D in patients with dementia

Abstract: There are measurement difficulties associated with the assessment of health-related quality of life (HRQL) in older people with dementia. The use of proxies is a commonly employed approach to overcome such problems. The research reported in this paper sought to identify, specifically for the EuroQol EQ-5D HRQL instrument, whether construct validity is greater for 'family caregivers' or 'clinicians' as two alternative sources of proxy information for patients with a diagnosis of dementia. This involved the expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
100
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(104 citation statements)
references
References 30 publications
3
100
0
1
Order By: Relevance
“…The instruments used may not be sensitive enough to show an improvement in length and quality of life as a result of an intervention. Given that proxies (i.e., spouse or caregiver) consistently provide lower ratings than the person themselves [28], for individuals with mild to moderate dementia (mini-mental state examination (MMSE) score of 15-23), we recommend that health-related quality of life measures such as the EQ-5D, SF-6D, or HUI3 be collected with interviewer assistance. For individuals with a MMSE score below 15, we recommend proxy assessment [29].…”
Section: Choice Of Generic Versus Disease-specific Instruments To Assmentioning
confidence: 99%
“…The instruments used may not be sensitive enough to show an improvement in length and quality of life as a result of an intervention. Given that proxies (i.e., spouse or caregiver) consistently provide lower ratings than the person themselves [28], for individuals with mild to moderate dementia (mini-mental state examination (MMSE) score of 15-23), we recommend that health-related quality of life measures such as the EQ-5D, SF-6D, or HUI3 be collected with interviewer assistance. For individuals with a MMSE score below 15, we recommend proxy assessment [29].…”
Section: Choice Of Generic Versus Disease-specific Instruments To Assmentioning
confidence: 99%
“…The vast majority of studies excluded these patients from their analyses and, when this does not occur, there are uncertainties regarding the use of EQ-5D for these patients. For some authors, the fact that EQ-5D does not directly measure cognition should interfere (Bryan et al, 2005;Davis, 2010), others authors focus the discussion on the capacity of these patients to asses health-related quality of life using the EQ-5D instrument (Coucill et al, 2001;De Rooij et al, 2008;Gjertsen, 2010). There is a need for new research on the evaluation of the level of dementia that patients would become unable to reply the questionnaire.…”
Section: Discussionmentioning
confidence: 99%
“…There are differences between the assessments done by the patients and those done by their relatives/caregivers or clinician (Coucill et al, 2001;Bryan et al, 2005;Gjertsen, 2010). In a study with 64 patients with dementia, the overall valuation EQ-5D scores based on clinicians' answers was significantly higher than the score based on caregivers evaluation, and it was found more correlation clinicianpatient for mobility and safe care (more observable dimensions) and caregiver-patient for usual activities and anxiety/ depression (subjective dimensions) (Bryan et al, 2005). Although Blomfeldt et al (2005) observed low correlation between caregiver-patient for pain and anxiety/depression, they stated that the use of proxies is the only way to assess the HRQOL for cognitive impaired patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that older patients with cognitive impairment may have difficulty understanding the concept of quality of life, and may lack insight into their functional ability [Bryan et al, 2005;Hulme et al, 2004;Novella et al, 2006]. In this study, a total of 19 participants were defined by the occupational therapist [applying the Modified Rankin Scale] as grade 4 -having a moderately severe disability [defined as being unable to walk and attend to own bodily needs without assistance] on the scale of 1 to 5 where 1=no symptoms at all and 5=severe disability.…”
Section: Icecap-o Eq-5dmentioning
confidence: 99%